2015
DOI: 10.1787/5jrxm4dhv9r2-en
|View full text |Cite
|
Sign up to set email alerts
|

The causes and consequences of field-of-study mismatch

Abstract: OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are welcomed, and may be sent to the Directorate for Employment, Labour and Social Affairs OECD,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 20 publications
0
33
0
9
Order By: Relevance
“…Furthermore, field-of-study mismatch is above the OECD average in Poland, implying economy-wide costs in terms of productivity losses, a higher incidence of unemployment and sunk costs for training in a field not corresponding to the worker's ultimate job (Montt, 2015). At the same time, many employers report difficulties in finding suitable candidates, such as professionals in science and engineering, education and healthcare, as well as qualified workers in industry and construction (Kocór et al, 2015).…”
Section: Effects (Adalet Mcgowan and Andrews 2015)mentioning
confidence: 99%
“…Furthermore, field-of-study mismatch is above the OECD average in Poland, implying economy-wide costs in terms of productivity losses, a higher incidence of unemployment and sunk costs for training in a field not corresponding to the worker's ultimate job (Montt, 2015). At the same time, many employers report difficulties in finding suitable candidates, such as professionals in science and engineering, education and healthcare, as well as qualified workers in industry and construction (Kocór et al, 2015).…”
Section: Effects (Adalet Mcgowan and Andrews 2015)mentioning
confidence: 99%
“…The Survey of Adult Skills provides a unique source of information on the match between workers and the skills demands of their jobs, in terms of qualifications, field of study, and proficiency in literacy, numeracy and problem solving. Mismatches between adults' skills and what is required or expected of them at work are found to be pervasive, but generate negative outcomes for workers when related to overqualification (Montt, 2015) or negative outcomes for economies when related to over-or underskilling (Adalet McGowan and Andrews, 2015). On average, about 22% of workers reported that they are overqualified (i.e.…”
Section: Mismatches Of Qualifications and Skillsmentioning
confidence: 99%
“…At the firm level, there may be incentives to hire overqualified workers: they are more productive, as indicated by their wages. But, on aggregate, these workers and the economy would be better off if they were working at their adequate qualifications level (Montt, 2015). The effect of overskilling on wages is small and often not statistically significant.…”
Section: Mismatches Of Qualifications and Skillsmentioning
confidence: 99%
See 2 more Smart Citations